PORTAL VEIN THROMBOSIS AND CAVERNOUS TRANSFORMATION IN TWO PATIENTS WITH PEPTIC ULCER - Gonca TATAR; Esin ÖZYILKAN; Ferhun BALKANCI; Burhan KAYHAN; Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-